Changing between representations of elementary functions: students’ competencies and differences with a specific perspective on school track and gender - Sproesser, Ute; Vogel, Markus; Dörfler, Tobias; Eichler, Andreas (International journal of STEM education, 2022)
Functional thinking is characterized as a specific way of thinking in relationships, dependencies, and changes. Hence, beyond mathematics, it is also crucial for other (STEM) disciplines as well as for everyday situations. In particular, dealing with different representations of functions and changing between them are core function-related competencies, which are correspondingly needed for the formation of appropriate concepts and flexible problem-solving in various situations. Therefore, this study investigated students’ (N = 856) competencies related to representational changes of elementary functions and, in particular, assessed which changes are especially easy or difficult for students. Moreover, possible school track and gender differences were investigated by performing DIF analyses within the framework of Rasch modeling. The data were gathered using a paper-pencil test administered after the students had completed the teaching unit on linear functions in their mathematics lessons.